Beyond the Liver ! Extra Hepatic Manifestations: Assessment of Frequency and Risk Factors among Hepatitis B & C related Chronic Liver Diseases (Medical Forum Monthly, 2024)
Objectives: The study aimed to determine the frequency and risk factors for Extra Hepatic Manifestations among patients with Hepatitis B and C related Chronic Liver Diseases.Study Design: Cross Sectional StudyPlace and Duration of Study: This Study is conducted at the Department of Medicine (Both indoor & outdoor patients) of Civil Hospital, Karachi from 2012 to 2016.Materials and Methods: In this study of 548 patients, who were positive for HBV or HCV, fulfill the selection criteria and were suffering from Chronic Hepatitis, Cirrhosis or HCC were examined for Extra Hepatic Manifestations clinically and if required appropriate tests were done to confirm the diagnosis & finding. Frequency and risk factors were determined for extra hepatic manifestations. Test of statistical significance were applied where p value of <0.05 was considered to be statistically significant cut-off.Results: Majority of patients 432 (78.8%) were HCV Positive and 116 (21.2%) were found to be HBV positive. Overall frequency of extra hepatic manifestations was found to be 54.7 %. Patients with chronic hepatitis C and B. The Extra Hepatic Manifestations of 60.6 % in HCV and 32.8% in HBV respectively. Diabetes Mellitus (DM) is the most common extra hepatic manifestation found in both, chronic HCV (19.0%) and chronic HBV patients (5.2%) whereas hypertension is the second commonest extra hepatic manifestation among HBV patients (12.1%). Disease duration > 5 years, age> 45 years, Viral PCR, Raised ALT and Hepatocellular Carcinoma associated with chronic HCV and HBV were found to be significant risk factors for extra hepatic manifestations.Conclusion: Extra Hepatic Manifestations are more common in HCV associated liver diseases than HBV. Diabetes and hypertension are the main extra hepatic manifestation among HBV & HCV positive patient. Disease duration > 5 years, age> 45 years, Viral PCR, Raised ALT and HCC associated with chronic HCV and HBV were found to be significant risk factors for Extra Hepatic Manifestation